Laporan Kasus Pyoderma Gangrenosum disertai Kandidiasis Kutis pada Wanita dengan Sindrom Metabolik - Ambar Aliwardani; Fiska Rosita; Putti Fatiharani; Endra Yustin Ellistasari (PT Dexa Medica, 2022)
Introduction: Pyoderma gangrenosum (PG) is a rare inflammatory disease characterized by sterile, predominantly neutrophilic infiltration of the skin and other organs. PG is found particularly in women aged between 40-60 years. Metabolic syndrome is reported to have a potential role to induce PG. Case: A 45-year-old woman came to Dr. Moewardi Hospital with chief complaints of ulcer in the chest and legs that was preceded by reddish fluid filled bump which then broke into painful wound. History of trauma, gastrointestinal, and joint pain was denied. Dermatological examination of anterior trunk region and inferior extremity showed erythematous patches with multiple ulcers with irregular border covered with hemorrhagic crusts and necrotic tissue. Pathergy test was negative. In the right and left axillary, inframammary and inguinal, there were hyperpigmented patches with scales and satellite lesions, KOH 10% examination obtained pseudohyphae and cell budding. The patient also has metabolic syndrome. Diagnosis of PG was made based on the presence of 2 major and 2 minor criteria. Patient was given intravenous methylprednisolone 93.75 mg/24 hours, analgesics, antibiotics, topical antifungals, debridement and breast reconstructive surgery after response to steroid therapy was seen. The patient was discharges from hospital with improvement. Discussion: Metabolic syndrome is considered to be a risk factor contributing to the development of systemic chronic inflammatory processes and has been described as one of the precipitating factors for PG and skin candidiasis. Management of metabolic syndrome as the known risk factor aims to minimize the recurrence of PG in the future.